EVALUASI TEBAL PERKERASAN OPRIT JEMBATAN BAWAS DENGAN MENGGUNAKAN MANUAL DESAIN PERKERASAN JALAN NO. 02/M/BM/2013 - Juliarsih, Santi; Widodo, Slamet; Sumiyattinah, - (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
One of the government's efforts in equitable economic development is by providing bridge infrastructure. To connect the bridge to the highway, a bridge approach (oprit) is required, where the bridge oprit is a segment connecting the pavement construction with the bridge abutment. One of the existing bridge construction in West Kalimantan is Bawas Bridge which has been completed in 2015. The author calculates the construction of Bawas bridge oprit that has been installed in the field on the basis of existing theory, whether it meets the requirements or not according to existing planning standards.The calculation refers to the Road Pavement Design Manual Number 02 / M / BM / 2013. The required data are Planning Layout, Land Data Parameter, LHR Data of Pontianak - Tayan road section. The calculation stage is starting from calculating bridge oprit foundation, pavement thickness and retaining wall. Calculations based on existing dimensions of the field are then recalculated on the basis of existing theory.The result of the calculation is the foundation using a 20x20 cm concrete piling pole with a depth of 12.00 meters and the distance between the poles of 2.00 meters; pavement thickness using rigid pavement as thick as 31.00 cm, LMC 15.00 cm and Class A Aggregate Base 15.00 cm thick; as well as retaining wall using pre-cast concrete spun pile á´“40 with depth of mounting 38,00 meters and precast concrete sheet pile W-400 with depth of mounting 12,00 meter. The results of these calculations are presented in the form of appendix of engineering drawings.Â Keywords: Basic soil improvement; bridge oprit planning; MDPJ No. 02 / M / BM / 2013